Comprehensive improvement of nutrients and volatile compounds of black/purple rice by extrusion-puffing technology - Ma, Yanrong; Li, Jiaxing; Xue, Yan; Xu, Yunbi; Liu, Chunming; Su, Dingding (Frontiers in Nutrition, 2023)
Black/purple rice is a pigmented rice variety that contains high levels of anthocyanins, flavonoids, and other valuable bioactive compounds. Owing to its robust anti-inflammatory and antioxidant properties, black/purple rice exerts a beneficial effect on human health. Extrusion puffing technology has emerged as a promising means of improving rice flavor with lesser effect on nutrient content. In this study, metabolomics approach was used to conduct comprehensive metabolomics analyses aimed at examining the impact of extrusion puffing on black/purple rice nutritional value and flavor. These analyses revealed that following extrusion puffing, black/purple rice exhibited significant improvements in the content of nutrients including flavonoids, minerals, and proteins together. Extrusion puffing additionally increased the diversity of volatile compounds within black/purple rice. Overall, these findings provide a robust theoretical foundation for the use of extrusion puffing technologies as a processing approach amenable to healthy food production.